Pemberian Vitamin A Pada Anak Di Daerah Pesisir Pantai Sumpang Binangae Wilayah Kerja Puskesmas Padongko Kabupaten Barru - Mulat, Trimaya Cahya; Abdullah, Rusli; Jaya, Rachmat; Latif, Sarifudin Andi; Zaenal, Zaenal; Marpaung, Mauritz Pandapotan (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Vitamin A is the most essential nutrient, this is because our food consumption is not sufficient and is still low so it must be met from outside. Vitamin A is a vitamin that has many properties for reducing mortality and morbidity rates, and is beneficial for human growth, and also plays a role in the body's immune system, protecting the body from contracting various infections. A deficiency of vitamin A can cause night blindness, which is another form of xeropthalmia including damage to the cornea and blindness. From the explanation of the various benefits of vitamin A itself, it is very important to meet the daily needs of vitamin A, especially for children and toddlers who are still in the process of growing in order to avoid various diseases ranging from eye diseases, growth and nutritional problems to infectious diseases. can endanger lives. The aim of this service is to educate the public about the correct use of vitamins and the importance of fulfilling nutrition, especially vitamin A for children. The method used in this activity is presentation of material, question and answer between the presenter and the village community, filling in the pretest and posttest. This service activity provides material understanding regarding the benefits of giving vitamin A to children as evidenced by increased knowledge after socialization and understanding of the community in the Coastal Coastal Village of Sumpang Binangae regarding Vitamin A in children.